Stratigraphy and palaeoenvironment of Upper Miocene diatomaceous mudstones (Coquimbo Formation) at Tongoy, Chile - Patrick Grunert; Rafael Carballeira; Stephanie Scheidt; Tiago Menezes Freire; Sven N. Nielsen; Marcelo M. Rivadeneira; Fatima Zohra Bouhdayad; Pablo Oyanadel-Urbina; Norbert R. Nowaczyk; Jassin Petersen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Constraints on the use of cosmogenic beryllium isotopes for synchronizing marine sediments and ice cores - Julia Loftfield; Norbert Nowaczyk; Lester Lembke-Jene; Thomas Frederichs; Johannes Lachner; Frank Lamy; Georg Rugel; Konstanze Stübner; Florian Adolphi (Earth and Planetary Science Letters, 2025)

Properties of novel LX lunar regolith simulant system — the base simulants: Part 2 - Joel Patzwald; Rafael Kleba-Ehrhardt; Tjorben Griemsmann; Norbert Nowaczyk; Stefan Linke; Ludger Overmeyer; Enrico Stoll; David Karl (Planetary and Space Science, 2025)

Pervasive Millennial-Scale Interstadial/Interglacial Climate Variability in the High-Latitude Northern Hemisphere - Steve P. Lund; Norbert Nowaczyk; Lloyd Keigwin; Jens Gruetzner (Journal of Marine Science and Engineering, 2025)
IODP Ex. 323 to the Bering Sea recovered a detailed record of Quaternary environmental variability adjacent to Alaska and eastern Siberia. The deep-sea sediment records show a dramatic bimodal environmental record of alternating high versus low magnetic susceptibility. Oxygen isotope records indicate that the interglacials are times of high clastic flux (high magnetic susceptibility) from the adjacent continents into the Bering Sea. Subsequent, more detailed chronostratigraphy indicates that Interstadial 3 and Interglacials 5, 7, and 9 are also intervals of large-amplitude, millennial-scale environmental variability alternating between warmer/wetter and cooler/drier intervals, with a quasi-cyclicity of ~5000 years. Comparative studies of North Atlantic Quaternary sediments associated with ODP Leg 172, with a similar dramatic glacial/interglacial variation in carbonate, show an almost identical millennial-scale (~5000 yrs) pattern of variability that we attribute to alternating warmer/cooler intervals in Interstadial 3 and Interglacials 5, 7, and 9. These results can also be compared to findings for Lake Elgygytgyn in Siberia. The chronology of this record is less certain than those of the other two regions, but it, too, shows large-amplitude changes in magnetic susceptibility in Interstadial 3 and Interglacials 5, 7, and 9 that can be attributed to oscillating warmer/cooler conditions on a millennial scale. These results suggest a coherent, hemispheric-scale pattern of climate variability in interstadial/interglacial periods of the last 400 ka with a quasi-cyclicity of ~5000 years. We speculate that this cyclicity is driven by a harmonic of the chaotic precession Milankovich cyclicity.

Causes and consequences of natural and anthropogenically induced late Holocene hydrological variations on the largest freshwater system in the Lesser Caucasus (Lake Sevan, Armenia) - Torsten Haberzettl; Marie-Luise Adolph; Taron Grigoryan; Hayk Hovakimyan; Thomas Kasper; Norbert Nowaczyk; Christian Zeeden; Lilit Sahakyan (Quaternary Science Reviews, 2024)

Climate variability in a 3.8 Ma old sedimentary record from the hyperarid Atacama Desert - Felix L. Arens; Jenny Feige; Alessandro Airo; Christof Sager; Lutz Hecht; Lucas Horstmann; Felix E.D. Kaufmann; Johannes Lachner; Thomas Neumann; Norbert Nowaczyk; Ferry Schiperski; Peter Steier; et al. (Global and Planetary Change, 2024)

Revised age and stratigraphy of the classic Homo erectus-bearing succession at Trinil (Java, Indonesia) - Sander L. Hilgen; Eduard Pop; Shinatria Adhityatama; Tom A. Veldkamp; Harold W.K. Berghuis; Indra Sutisna; Dida Yurnaldi; Guillaume Dupont-Nivet; Tony Reimann; Norbert Nowaczyk; Klaudia F. Kuiper; Wout Krijgsman; et al. (Quaternary Science Reviews, 2023)

Cooling rates of pyroclastic deposits inferred from mineral magnetic investigations: a case study from the Pleistocene Mýtina Maar (Czech Republic) - Philipp Lied; Agnes Kontny; Norbert Nowaczyk; Jan Mrlina; Horst Kämpf (International Journal of Earth Sciences, 2020)
Tephra layers of the Mýtina Maar, Czech Republic, contain ferrimagnetic Mg–Al-rich titanomagnetite, which is suggested to originate from a fractionated alkaline CO 2 -rich lithospheric mantle melt. We investigated the magnetic mineralogy and Curie temperature ( T C ) from tephra deposits of two drill cores (< 9 m depth). T C calculated (208 ± 14 °C) from chemical composition (Fe 2+ 0.8 Mg 0.5 Fe 3+ 1.1 Al 0.3 Ti 0.3 O 4 ) is in accordance with T C retrieved from cooling curves of temperature-dependent magnetic susceptibility measurements (195–232 °C). However, thermomagnetic curves are irreversible either with lower (type I) or higher (type II) T C in the heating curve. All curves show transition temperatures above ca. 390 °C, indicating maghemitization. We interpret the irreversibility of T C (∆ T C ) in terms of different degrees of cation ordering, overprinted or masked by different degrees of maghemitization, which is a low-temperature phenomenon. Negative ∆ T C indicates that original deposited titanomagnetite has cooled faster and, therefore, has stored a lower degree of cation ordering compared to heating/cooling rate of 11 °C/min in the Kappabridge. Type II with positive ∆ T C indicates higher degree of cation ordering, and, therefore, slower cooling rate. The central part of this deposit shows most severe maghemitization, indicating rather wet emplacement. We, therefore, suggest different eruption styles for deposition of type I pyroclastics with more phreatomagmatic and type II pyroclastics with more phreato-Strombolian eruption styles. Our study is a new approach to discriminate different cooling histories in maar deposits using the Curie temperature of titanomagnetite. We suggest that this method has the potential to discriminate different emplacement modes resulting from different eruption styles.

Palaeo- and rock magnetic investigations of Late Quaternary sediments from the Upper Congo deep-sea fan: on the difficulty in obtaining palaeomagnetic secular variation records from low latitudes - Ute Frank; Norbert R. Nowaczyk; Thomas Frederichs; Jiabo Liu; Monika Korte (International Journal of Earth Sciences, 2019)

Holocene paleohydrological reconstruction of Lake Strzeszyńskie (western Poland) and its implications for the central European climatic transition zone - Krzysztof Pleskot; Rik Tjallingii; Mirosław Makohonienko; Norbert Nowaczyk; Witold Szczuciński (Journal of Paleolimnology, 2018)

Modification of climate signals by human activities recorded in varved sediments (AD 1608–1942) of Lake Holzmaar (Germany) - Ulrike Kienel; Heinz Vos; Peter Dulski; Andreas Lücke; Robert Moschen; Norbert R. Nowaczyk; Markus J. Schwab (Journal of Paleolimnology, 2013)

Origin of magnetic anomalies in the large Ebersbrunn diatreme, W Saxony, Germany - Alina Schmidt; Norbert Nowaczyk; Horst Kämpf; Irka Schüller; Christina Flechsig; Thomas Jahr (Bulletin of Volcanology, 2013)

A tephrostratigraphic record for the last glacial–interglacial cycle from Lake Ohrid, Albania and Macedonia - Hendrik Vogel; Giovanni Zanchetta; Roberto Sulpizio; Bernd Wagner; Norbert Nowaczyk (Journal of Quaternary Science, 2010)
Here we present a tephrostratigraphic record (core Co1202) recovered from the northeastern part of Lake Ohrid (Republics of Macedonia and Albania) reaching back to Marine Isotope Stage (MIS) 6. Overall ten horizons (OT0702‐1 to OT0702‐10) containing volcanic tephra have been recognised throughout the 14.94 m long sediment succession. Four tephra layers were visible at macroscopic inspection (OT0702‐4, OT0702‐6, OT0702‐8 and OT0702‐9), while the remaining six are cryptotephras (OT0702‐1, OT0702‐2, OT0702‐3, OT0702‐5, OT0702‐7 and OT0702‐10) identified from peaks in K, Zr and Sr intensities, magnetic susceptibility measurements, and washing and sieving of the sediments. Glass shards of tephra layers and cryptotephras were analysed with respect to their major element composition, and correlated to explosive eruptions of Italian volcanoes. The stratigraphy and the major element composition of tephra layers and cryptotephras allowed the correlation of OT0702‐1 to AD 472 or AD 512 eruptions of Somma‐Vesuvius, OT0702‐2 to the FL eruption of Mount Etna, OT0702‐3 to the Mercato from Somma‐Vesuvius, OT0702‐4 to SMP1‐e/Y‐3 eruption from the Campi Flegrei caldera, OT0702‐5 to the Codola eruption (Somma‐Vesuvius or Campi Flegrei), OT0702‐6 to the Campanian Ignimbrite/Y‐5 from the Campi Flegrei caldera, OT0702‐7 to the Green Tuff/Y‐6 eruption from Pantelleria Island, OT0702‐8 to the X‐5 eruption probably originating from the Campi Flegrei caldera, OT0702‐9 to the X‐6 eruption of generic Campanian origin, and OT0702‐10 to the P‐11 eruption from Pantelleria Island. The fairly well‐known ages of these tephra layers and parent eruptions provide new data on the dispersal and deposition of these tephras and, furthermore, allow the establishment of a chronological framework for core Co1202 for a first interpretation of major sedimentological changes. Copyright © 2009 John Wiley & Sons, Ltd.

Magnetic properties and environmental changes recorded in Lake Lehmilampi (Finland) during the Holocene - Eeva Haltia-Hovi; Norbert Nowaczyk; Timo Saarinen; Birgit Plessen (Journal of Paleolimnology, 2010)

A 40,000-year record of environmental change from ancient Lake Ohrid (Albania and Macedonia) - Bernd Wagner; André F. Lotter; Norbert Nowaczyk; Jane M. Reed; Antje Schwalb; Roberto Sulpizio; Verushka Valsecchi; Martin Wessels; Giovanni Zanchetta (Journal of Paleolimnology, 2009)

Secondary Fe–Mn-oxides in minerals heavily damaged by α-recoil: possible implications for palaeomagnetism - Rolf L. Romer; Norbert Nowaczyk; Richard Wirth (International Journal of Earth Sciences, 2007)

Luminescence geochronology for sediments from Lake El’gygytgyn, northeast Siberia, Russia: constraining the timing of paleoenvironmental events for the past 200 ka - Steven L. Forman; James Pierson; Jeaneth Gómez; Julie Brigham-Grette; Norbert R. Nowaczyk; Martin Melles (Journal of Paleolimnology, 2006)

Sedimentary geochemistry of core PG1351 from Lake El’gygytgyn—a sensitive record of climate variability in the East Siberian Arctic during the past three glacial–interglacial cycles - Martin Melles; Julie Brigham-Grette; Olga Yu. Glushkova; Pavel S. Minyuk; Norbert R. Nowaczyk; Hans-W. Hubberten (Journal of Paleolimnology, 2006)

A revised age model for core PG1351 from Lake El’gygytgyn, Chukotka, based on magnetic susceptibility variations tuned to northern hemisphere insolation variations - Norbert R. Nowaczyk; Martin Melles; Pavel Minyuk (Journal of Paleolimnology, 2006)

Sedimentological evidence for environmental changes since 34,000 years BP from Lago di Mezzano, central Italy - Antje Ramrath; Norbert R. Nowaczyk; Jörg F.w. Negendank (Journal of Paleolimnology, 1999)

Near East Desertification: Evidence from the Dead Sea - Christoph Heim; Norbert R. Nowaczyk; Jörg F. W. Negendank; Suzanne A. G. Leroy; Zvi Ben-Avraham (The Science of Nature, 1997)